0152 A functional role for global slow oscillations in major depressive disorder with hypersomnia. (25th May 2022) - Malerba, Paola; Dave, Abhishek; Cook, Jesse; Mednick, Sara; Plante, David
Abstract: Introduction: Sleep slow oscillations (SOs, 0.5-1.5Hz) during stages N2 and N3 sleep facilitate cortical communication and are important to the restorative properties of sleep. Spatiotemporal clustering analysis of SOs on the electrode manifold has identified 3 topographically distinct patterns of SOs: Frontal, Local, and Global. Global SOs are spatially widespread cortical events implicated in anterior-posterior long-range communication. However, their precise functional significance is not fully understood. Patients experiencing Major Depressive Disorder (MDD) with comorbid hypersomnia show local deficits in parieto-central slow wave activity, suggesting that frontally-initiated SOs are not propagating to parietal-central regions. Hypersomnolence in MDD may therefore be connected to insufficiently restorative sleep. Here, we retrospectively examine associations between Global SOs in N2 and N3 sleep and hypersomnia severity in healthy controls and MDD patients. Methods: MDD patients with (n=22) and without (n=22) hypersomnia, and age-gender balanced healthy controls (n=22) underwent overnight polysomnography studies with 256-channel hdEEG. After detection of SOs, our previously developed classification method was applied retrospectively to all SOs in this dataset, including leveraging a k-means clustering algorithm naïve to the MDD/Hypersomnia label. Fractions of global SOs during stages N2 and N3 were compared across healthy controls and MDD patients. Finally, the fraction of global SOs occurring during the night was correlated against all subjects' individual scores on the Hypersomnia Severity Index (HSI). Results: Analysis of EEG data revealed pronounced, but not statistically significant deficits in global SOs during N3 sleep in MDD patients with comorbid hypersomnia. These deficits were significantly correlated with HSI when examining MDD patients together (Pearson's r = -0.397, p<0.01). Conclusion: Our findings suggest that MDD patients with higher hypersomnia severity experience more pronounced deficits in Global SOs. Given the importance of SOs for the restorative properties of sleep, it is possible that MDD patients with hypersomnia might incur an enhanced sleep need driven by the homeostatic cost of a deficit in Global SOs.. Future studies are necessary to investigate causal mechanisms underlying these findings. Support (If Any): American Sleep Medicine Foundation (76-JF-12), Brain and Behavior Research Foundation (19193), and NIMH (K23MH099234) to DTP.